SISTEM NOTIFIKASI UNTUK KEAMANAN RUMAH BERBASIS SENSOR VISUAL - Diah Arista Ningsih, Ni Putu; Wiharta, Dewa Made; Putra Sastra, Nyoman (Jurnal SPEKTRUM; Vol 6 No 1 (2019): Jurnal SPEKTRUM, 2019)
In this tool utilizing the Raspberry Pi and Arduino Uno Microcontrollers as equipment that can provide a good level of security for home security with visual sensor based. This tool uses an electronic key where you can electronically open and lock the door based on the password inputted using the keypad. The whole system on the electronic key is fully controlled by the Arduino Uno Microcontroller and if the password inputted on the keypad is more than three times wrong, an buzzer will ring, the camera will take a picture and the Raspberry Pi Microcontroller will immediately send a notification to the homeowner via the Telegram application. . When someone wants to try to get into the house by using the correct or wrong password the camera will still automatically take pictures and will immediately send notifications in the form of text and images to the homeowner through the Telegram application. In conditions far from home the homeowner can also find out the current state of the house through the Telegram application. In the system this tool uses a password where passwords can be stored in the form of "hard code", the average delay in each experiment of this tool is around three minutes.